Spectroscopic evidences of toxic trans‐crotonaldehyde trapped and transformed by resveratrol to prevent the damage of mitochondrial DNA. Issue 7 (16th April 2017) - Su, Yanbin; Chen, Lei; Su, Yanwen; Li, Zhengqiang; Zhang, Chuang; Mu, Tongxing
Abstract: The purpose of this study is to probe the spectroscopic evidences of toxic trans‐crotonaldehyde (TCA) trapped and transformed by resveratrol (Res) to prevent the damage of mitochondrial DNA. In aldehyde dehydrogenase (ALDH) at the different pH or mitochondria, the spectroscopic characteristics of TCA trapped and transformed by Res were observed by means of both UV‐vis and Raman spectra. When Res interacted with TCA, TCA peak at 316 nm immediately disappeared while Res main peak at 305 nm and shoulder peak at 320 nm were dramatically changed, Raman peaks of TCA at 1, 688 cm −1 assigned to CHO and 1, 641 cm −1 affiliated to CC were strikingly shifted, Raman peaks of Res itself were significantly displaced or disappeared, especially in mitochondria and ALDH at different pH. The active groups of Res were the OH at C5 and C10 . The results of theoretical calculations are in agreement on the whole with the experimental data. The Res plays undoubtedly an important role via the structural change in TCA. The toxic CHO of TCA was effectively trapped and transformed by Res by means of itself OH at C5 and C10 . The mitochondrial alkaline microenvironment and ALDH promoted the elimination of toxic TCA. © 2017 IUBMB Life, 69(7):500–509, 2017